Desenvolvimento de método de amostragem de agrotóxicos em águas utilizando nanotubos de carbono e determinação por cromatografia gasosa acoplada à espectrometria de massas - Frederico Hayala Fernandes Barbosa (2015)
World population growth causes a great demand for food, which must have good quality and durability. The pesticides are important products for the control and prevention of harmful organisms, minimizing losses, increasing the quality and quantity of the products obtained. However, most pesticides are harmful and can cause environmental and food contamination problems. The risk of pesticides exposure requires controled use of these compounds and the development of efficient methods for their identification and quantification. This work presents the development of a new multiresidue method for pesticides analysis in water by gas chromatography coupled to mass spectrometry (GC/MS). The proposed extraction procedure was based on the use of carbon nanotubes amphiphilics and hybrids with magnetic properties (mCNT). The mCNT used were produced in the Department of chemistry at UFMG. They have multiple-walled structures (MWNTC) and are composed of a hydrophobic and a hydrophilic fraction (doped with nitrogen). That hybrid constitution allows their total dispersion in water and at the same time a high efficiency for the sorption of pesticides. Besides, the magnetic property allows easy removal of the mCNT from the solution. Therefore, a small amount of mCNT is required for extraction, and after separation from the solution by a magnet these are mCNT desorbed with micro amounts of solvents. The 19 pesticides studied were extensively used in Minas Gerais State in cultures of pineapple, coffee, sugarcane, eucalyptus, papaya, passion fruit, melon, strawberry, grape and wheat. The study of method validation showed appropriate merit parameters to the quantification of 16 pesticides in water. The method presented good linearity in the range of 0.5 to 4.0 mg L-1 coefficients of determination were in the range of 0.904 to 0.973. The detection limits were in the range of 0.51 to 2.29 g L-1 and the quantification limits between 1.19 to 5.35 g L-1.The recovery ranged from 79.9 to 111.6 %. The method application was realised by analyzing 48 water samples collected at various locations in the State of Minas Gerais. 10 samples were contaminated with 6 pesticides, kresoxim methyl, trifluralin, terbufos, disulfoton, alachlor and buprofezin.